PENERAPAN TARGET COSTING SEBAGAI ALAT BANTU PERENCANAAN BIAYA PADA UMKM KEBAB BATUBARA SANGATTA KUTAI TIMUR - Wahyu Mardiana; Amiruddin Amiruddin; Nanok Fitriyadi (Sekolah Tinggi Ilmu Ekonomi Nusantara Sangatta, 2023)
The purpose of this study is to analyze the application of target costing to reduce production costs so that the profit of MSME businesses can be increased. This research was conducted at UKM Kebab Coal, Sangatta, East Kutai. The type of research used is descriptive quantitative. Data collection methods are interviews and documentation. The results of the study show that applying target costing can reduce production costs incurred and increase profits. Where before implementing target costing the production costs incurred amounted to Rp. 6,771,500 but after the target costing concept was applied production costs could be reduced to Rp. 7,883,583.33, while the expenditure was greater due to business actors / MSMEs previously not calculating overhead costs in calculations production cost